Belowground Biomass Dynamics in Deciduous and Evergreen Tree Species in a Juvenile Block Plantation in Central India - Pandey, C.B. (Indian Journal of Agroforestry, 2020)
Season variation in tap root biomass, coarse root biomass and fine root biomass and their distribution along the soil depth was evaluated in two deciduous (Albizia Iebbeck and A. procera) and an evergreen tree species (Acacia nilotica) in a two years old block plantation in central India, Course root biomass ranged from 2.46 to 4.0 g plant-1 in A. Iebbeck, 1.13 to 3.01 g plant-1 in A. procere and 0.24 to 0.65 g plant-1 in A nilotica in 0-10 cm depth of the soil. Similarly, fine root biomass was 0.48 to 1.81 g plant-1 in A lebbeck 0.22 to 1.34 g plant-1 in A. procera and 0.15 to 0.30 9 plant-1 in A nilotica in the upper soil depth (0-10 cm). In deciduous tree species root biomass increased from March to October, whereas in evergreen species it increased gradually over the time. Tap root biomass contributed maximum 84 to 87 % of the total root biomass in A. lebbeck, 85 to 87 % in A procera and 83to 91% in A nilotica. However, fine root biomass contributed minimum 0.86 to 3.12 % of total root biomass in A. lebbeck, 0.75 to 3.34 % in A. procera and 3.53 to 4.64 % in A. nilotica. Maximum root biomass in all the species were located in upper soil depth (0-l0 cm) and declined with increasing depth of the soil. Phased root growth along the soil depth was observed in all the species.